Perancangan Interior Restoran Museum Surabaya - Liong Ling Ling (Intra, 2016)
Siola building is a historic building that is enough for the city of Surabaya. Building full of history, applied to be cultivated for the city society, so that the Museum of Surabaya that was enacted in 2015, to improve the image of culture Surabaya. By doing so, to increase interest by many people who are not aware of any museum in Gedung Siola Surabaya, the need for support, so that their interior design Restaurant Museum Surabaya, because with a note that the restaurant can be interesting to the public. Because the modern world, not many people will always come in or aware of any museum in the absence of urgent necessity, so that with the design, it can make people interested to be without their special purposes in the museum. The location is so positioned in the city center, making this design is designed to meet the needs of the businessman who want to conduct meetings outside the office, seeing the needs of today, many people work or meet at a place to eat. The concept is applied is heroic to support a museum, by applying the traditional style that uses natural material as a supporter. So with their interrelationships with each other, will be at the museum Surabaya knowing by many people easily